Money market executive’s perception towards peer-to-peer (p2p) lending - KUMAR, DR. P. PRAVEEN; MS. YUVASREE. V, (The journal of contemporary issues in business and government, 2020)
Peer-to-Peer (P2P) refers to social lending and it is an emerging wealth management service that allows individuals to procure loans directly from investors without the intervention of a financial institution. P2P investors obtain better returns on their cash savings through lending in P2P lending platforms mostly through online web pages. The P2P model facilitates matching of individual investors with borrowers by assessing the creditworthiness on a periodical basis. P2P renders services for recovery of loan through this platform. Better interest rates are possible using these P2P online platforms. Borrowers who fail to obtain loans from traditional financial institutions can avail the services of these online platforms. The model also helps budding entrepreneurs to get their startups off the ground and it is a relatively new approach where borrowers can obtain loans from numerous individual investors pursuing multiple objectives when they pick loans to invest. Though P2P lending might seem like an attractive investment this is still a technically young industry.